Implementasi Prinsip Syariah dalam Manajemen Keuangan untuk Meningkatkan Pengambilan Keputusan Bisnis UMKM : Studi Kasus di Jakarta - Arief Syahreza; Aep Saefullah; Sukardi Sukardi; Suharmanto Suharmanto; Ujang Kusnaedi; Fisy Amalia (Pusat Riset dan Inovasi Nasional, 2025)
A unique problem in the implementation of sharia principles in MSMEs in Jakarta lies in the gap between the needs of sharia-based financial practices and the limited access and understanding of business actors. In fact, Jakarta as an economic center with the largest Muslim population in Indonesia has the potential to become an ideal model for sharia MSME financial management. This qualitative study examines the implementation of sharia principles in MSME financial management in Jakarta by focusing on three critical aspects: (1) the implementation of mudharabah (profit sharing) contracts, (2) the avoidance of usury, and (3) transaction transparency. Data was collected through in-depth interviews with 15 MSME owners, participant observations, and analysis of financial documents (2021–2023). The findings show that although MSMEs are committed to implementing sharia principles, the main challenges include limited understanding of sharia contracts, difficulties in separating personal and business finances, and the lack of affordable sharia financial instruments. In addition, it was found that most MSME actors still rely on conventional financing because Islamic banking procedures are considered more complicated and less flexible. The lack of mentoring and lack of access to formal training also exacerbate this condition. This study offers strategic solutions through strengthening Islamic financial literacy, providing contextual training modules, and intensive assistance based on the specific needs of MSMEs. In addition, collaboration between local governments, Islamic financial institutions, and business communities is needed to create an inclusive and sustainable Islamic financial ecosystem. The implications of the results of this study can be a reference for regulators and Islamic financial institutions in designing financing and education programs that are more adaptive to the characteristics of urban MSMEs.